Research on slag‐resistance of ZrN‐SiAlON‐SiC‐C composite refractory in different atmospheres. Issue 1 (19th September 2018) - Cheng, Bohao; Zhang, Zhijie; Wu, Xiaowen; Min, Xin; Huang, Zhaohui; Tao, Tianyi; Zhao, Haiqing; Fang, Minghao; Liu, Yan‐gai
Abstract: The ZrN‐SiAlON composite powder was synthesized using low‐grade zircon and bauxite by carbothermal reduction nitridation at first and then ZrN‐SiAlON‐SiC‐C composite refractory were fabricated with the ZrN‐SiAlON powder, SiC particles, and a small amount of Si powder as raw materials and sucrose as the binder. The slag resistance of these composites in O2, N2 and Ar atmosphere was investigated by X‐ray diffraction, scanning electron microscopy, and energy dispersion spectra. The results show that the pores in the inside of ZrN‐SiAlON‐SiC‐C composite refractory were enlarged in oxygen atmosphere due to oxidation, which leads to the decrease in slag resistance. In argon atmosphere, blast furnace slag destroyed the sintered body of zircon, corundum, and cristobalite with the formation of CaZrO3, then infiltrated into and filled the pores inside the refractory to form a dense layer, which hindered the further erosion of the blast furnace slag. In the reducing atmosphere, the interfacial energy of the gas‐liquid phases became larger due to the reactions between blast furnace slag liquid and the gas, resulting in a larger wetting angle which prevented the erosion.